Determination of the sensitivity range of biuret test for undergraduate biochemistry experiments - Janairo, Gerardo C. (Animo Repository, 2011)
Quantitation of the total protein content in a sample is a critical step in protein analysis. Molecular UV-Vis absorption spectroscopy is very efficient in quantitative analysis such as protein quantitation and has extensive applications in chemical and clinical laboratories worldwide. Among the various techniques for protein assay, biuret test is of particular interest in this study. This study sought to verify the sensitivity of biuret assay to protein samples with concentrations ranging from 0.0100 to 5.00 mg/mL. Albumin chicken egg was used as the protein sample. The assay was assessed to determine the range of concentration in which it will show linearity. The biuret test exhibited linearity in a wide range of concentrations (0.1000 ± 0.0004 to 5.00 ± 0.02 mg/mL). The starting protein concentration range established for the calibration curve of this assay is lower than the found literature value (1 mg/sample). The study provides a more workable range of biuret test.